A Novel Phosphorescent Iridium(III) Complex Bearing Formamide for Quantitative Fluorine Anion Detection - Song Guo; Chaoxiong Guo; Zhao Lu; Linlin Du; Man Gao; Shujuan Liu; Yuanli Liu; Qiang Zhao (Crystals, 2021)
Fluorine anion plays a critical role for human health, especially for the teeth and the skeletal system, and a deficiency or excess of fluorine anion will result in various diseases. Thus, the accurate and timely detection of fluorine content is of great importance. Herein, a novel and sensitive fluorine probe based on ionic iridium(III) complex using 5-formamide phenanthroline as an ancillary ligand was designed and synthesized rationally. The probe exhibited excellent performance for F− detection in organic solvents. H-bonding between the fluoride and the amide proton was formed, thus changing the photophysical properties of the probe and leading to significant phosphorescence quenching. Nuclear magnetic resonance titration and theoretical calculations were carried out to understand the mechanism in detail. This is the first report of an iridium(III) complex probe for F− detection based on the interaction between formamide and fluorine anion.